Between autonomy and responsibility. The philosophy of law and the legislation on the "right to die" - Palazzani, Laura (Medicina e Morale, 2022)
The article analyzes the end-of-life issues in bioethics from the perspective of the philosophy of law, critically analyzing the paths of the most recent legislation and jurisprudence in Italy. In particular, Law 219/2017 is analyzed with reference to the refusal and renunciation of life-saving treatments, the therapeutic obstinacy, deep sedation, advance care directives and care planning. The author analyzes the bioethical and bio-juridical problems between 'letting die' and 'killing', with reference to the sentence 242/2019 of the Constitutional Court which admits medically assisted suicide as an exception to art. 580 of the criminal code, under certain conditions. The sentence 50/2022 of the Constitutional Court on the inadmissibility of the so-called referendum on euthanasia allows to identify other bioethical reflections on the topics with reference to the minimum protection of life and vulnerability.